EVALUATING THE IMPACT OF CURRICULUM REFORMS ON ENGLISH LANGUAGE LEARNING ACROSS PRIMARY AND SECONDARY EDUCATION IN INDONESIA: A QUANTITATIVE STUDY - Kurnia Saputri; Aswadi Jaya; Darmawan Budiyanto (Indonesian EFL Journal, 2025)
Amid the national curriculum reform emphasizing communicative competence and digital integration, this study evaluates its impact on English language achievement across school levels in Indonesia. The study aims to analyze the effects of recent curriculum modifications on students’ English language performance across different grade levels. A quantitative approach was employed, involving 900 respondents consisting of elementary school students (grades 4–6), junior high school students (grades 7–9), and senior high school students (grades 10–12). Using a stratified random sampling technique, data were collected through validated instruments with reliability confirmed at Cronbach’s α > 0.70, ensuring consistent measurement. Data were analyzed using descriptive statistics, one-way ANOVA, Tukey HSD post-hoc test, and multilevel analysis. The results revealed an upward trend in English scores across higher grade levels, with the lowest mean score among elementary students (M = 65) and the highest among senior high school students (M = 72). The ANOVA test indicated significant differences among grade levels (F = 39.0, p < 0.001) with a medium effect size (η² = 0.08). The Tukey post-hoc test showed substantial differences between elementary and higher levels, while the difference between junior and senior high schools was relatively small. Multilevel analysis further revealed that 12% of the variance was attributable to teacher- or school-level factors, while individual differences remained the dominant contributor. These findings confirm that curriculum modifications significantly enhance students’ English language learning outcomes, particularly during the transition from elementary to secondary education.